Joint European League Against Rheumatism and European Renal Association–European Dialysis and Transplant Association (EULAR/ERA-EDTA) recommendations for the management of adult and paediatric lupus nephritis. Issue 11 (31st July 2012) - Bertsias, George K; Tektonidou, Maria; Amoura, Zahir; Aringer, Martin; Bajema, Ingeborg; Berden, Jo H M; Boletis, John; Cervera, Ricard; Dörner, Thomas; Doria, Andrea; Ferrario, Franco; Floege, Jürgen; et al.
Abstract : Objectives: To develop recommendations for the management of adult and paediatric lupus nephritis (LN). Methods: The available evidence was systematically reviewed using the PubMed database. A modified Delphi method was used to compile questions, elicit expert opinions and reach consensus. Results: Immunosuppressive treatment should be guided by renal biopsy, and aiming for complete renal response (proteinuria <0.5 g/24 h with normal or near-normal renal function). Hydroxychloroquine is recommended for all patients with LN. Because of a more favourable efficacy/toxicity ratio, as initial treatment for patients with class III–IVA or A/C (±V) LN according to the International Society of Nephrology/Renal Pathology Society 2003 classification, mycophenolic acid (MPA) or low-dose intravenous cyclophosphamide (CY) in combination with glucocorticoids is recommended. In patients with adverse clinical or histological features, CY can be prescribed at higher doses, while azathioprine is an alternative for milder cases. For pure class V LN with nephrotic-range proteinuria, MPA in combination with oral glucocorticoids is recommended as initial treatment. In patients improving after initial treatment, subsequent immunosuppression with MPA or azathioprine is recommended for at least 3 years; in such cases, initial treatment with MPA should be followed by MPA. For MPA or CY failures, switching to the other agent, or to rituximab, is the suggested course of action. In anticipation of pregnancy, patients should be switched to appropriate medications without reducing the intensity of treatment. There is no evidence to suggest that management of LN should differ in children versus adults. Conclusions: Recommendations for the management of LN were developed using an evidence-based approach followed by expert consensus.